Effect of Chromobacterium violaceum and quorum sensing on the growth of green bean (Vigna radiata) and plant growth promoting rhizobacteria (PGPR) - Loke, Wai Keong (2011)
Chromobacterium violaceum is a Gram-negative facultative anaerobic bacteria and pathogenic to human with high fatality rate. C. violaceum inhabits in soil and water in the tropical and subtropical regions of the world. The tropical climate in Malaysia offers a suitable environment for the growth of C. violaceum and it is believed that it is highly distributed in the soil and water in Malaysia. Soil is important in agriculture and the soil surface is most often in contact with people during their daily activities. However, the understanding of C. violaceum distribution has not been fully revealed especially in local soils and the effects on agriculture are still unknown. The production of antibiotics and hydrogen cyanide by C. violaceum was suspected as a possible compound that to give a negative impact on crops and beneficial microbes present in the soil. The main objective of this study was to determine the effect of Chromobacterium violaceum on plant-microbe interaction and quorum sensing mechanism. In this study, C. violaceum was isolated from 0-5 cm depth of the soil covered with grass surface in Universiti Putra Malaysia golf course and football field. We found the density of C. violaceum in 5 g soil were higher after a raining period about 1 X 107 c.f.u. in golf course and 7 X 107 c.f.u. in football field compared to usual non-rainy day where only 9 X 104 c.f.u. in golf course and 6 X 105 c.f.u. in football field. The C. violaceum also showed the oligophile characteristic that allowed them to grow in a wider range of soil and water areas. C. violaceum which reached quorum level inhibited the growth of green bean seedling as much as 86.5% for the shoot length and 92.1% for the root length. However inhibition was reduced to 37.5% for the shoot and 17.5% for root if the quorum level of C. violaceum was not reached under aseptic environment. Furthermore sterilized inoculant (killed) which has not reached quorum level did not affect the growth of green bean seedlings. These indicated that quorum sensing in Chromobacterium violaceum was a factor that determines its inhibitory effect on seedling growth. C. violaceum also have the same effect on PGPR where Chromobacterium violaceum that reached quorum level kill the selected PGPR; Azospirillum brasilense Sp7 (Gram negative), Rhizobium UPMR1102 (Gram negative) and Bacillus sphaericus UPMB10 (Gram positive). This study also showed that catabolite repression occurred in C. violaceum and the operon to controlling the genes for production of purple pigment and other antibiotics were catabolite-sensitive when the operon was not maximally expressed. The information about catabolite sensitivity in pathogenic C. violaceum can be a very useful tool in future research.